Revestimentos com materiais quasicristalinos via aspersão térmica: caracterização tribológica e microestrutural - Lima, Bruno Alessandro Silva Guedes de (2015)
By the excellent properties that present, the quasicrystals come if showing excellent protectors of metallic surfaces and their study as surface coatings is growing increasingly. In this work, was sprayed quasicrystals for methods HVOF an HVOF, in Steel substrata 1020, covers and aluminum.. In some samples, a Cu9Al4 alloy was sprayed between the substratum and the quasicristalino covering, to try to improve the adherence of the covering to the substratum and to protect the Quasicrystalline layer of contaminations. The coverings were characterized by the technique of DRX, optical microscopy and SEM. The study of microhardness and nanohardness in the surfaces of sprayed coverings was made. Finally, a tribological study of coatings was accomplished to evaluate the behavior of wear and friction of the layers and the adherence between them and substrata. These results will provide the basis for the use of these materials in parts and equipment used in industries. The layers obtained for LVOF had showed to one high degree of oxidation and a bad adherence with the substratum. The coverings obtained for HVOF had showed one high micro-hardness, with values between of 600 and 800HV. The values of nano hardness and modulus of elasticity that was found in the coatings are in accordance with the values found in literature. For the test of risk with spherical tip of 800μm, the critical loads of the risks were of 20N, for all the samples with exception of the Al-Qc sample. It did not have pullout in respect to substrate of coverings with 100μm of thickness and the results of the risk essays, was the same, independent of its nature, indicating that, for a thickness of 100μm, the quasicrystalline coatings behave as a massive material, facilitating the protection of the interfaces. Through the simulation tests, we could see that during the tests, for coatings with thicknesses of 100μm, the interfaces practically remain intact and they do not suffer plastic deformations. The simulation results corroborate with the tests of risks confirming that for a thickness of 100μm, the coverings behave as a massive material, independent of the nature of the substratum.